Bovine cysticercosis: a retrospective survey in the mountainous Region of Santa Catarina State, Brazil - Mayckon Antonio Cardoso Padilha; Gefferson Wasen; Daniela Barp Coffy; Antonio Pereira de Souza; Anderson Barbosa de Moura (Semina: Ciências Agrárias, 2018)
Bovine cysticercosis disease is prevalent worldwide, and is diagnosed frequently in slaughterhouses. This disease has an impact on animal production and public health due to Taenia saginata. In order to investigate the occurrence of bovine cysticercosis in the mountainous region of Santa Catarina state, Brazil, we performed a retrospective survey of beef carcasses that were positive for the parasite. We tabulated and analyzed the records of cattle that were slaughtered from 2003 to 2013, under the state inspection in Lages, Santa Catarina. These records were provided by Companhia Integrada de Desenvolvimento Agrícola de Santa Catarina (CIDASC). The data were analyzed using Chi-square test (P ? 0.05) to correlate the cysticerci occurrence with the independent variables. The animals were from the 18 municipalities that represent Associação dos Municípios da Região Serrana (AMURES). Among the animals that were slaughtered during the study period, 7.06% (1698/24055) were confirmed positive for cysticercosis during the visual inspection. Among the total cysts that were inspected, 25.79% and 74.20% were classified as viable and calcified, respectively. The most frequently parasitized organs were the head, with 876 cases (51.59%) positive for cysticerci (321 [36.64%] viable and 555 [63.36%] nonviable) and the heart with 641 cases (37.75%) positive for cysticerci (54 [8.42%] viable and 587 [91.58%] non-viable). In addition to the generalized infection (4.48%), the tongue and the diaphragm were the next most commonly parasitized organs, with 3.71% and 2.47% cases positive for cysticerci, respectively. There was no correlation (P > 0.05) between sex or age, and positive infection or cyst location. We identified statistical variations among the results for each of the evaluated years (P < 0.01). These reports indicated a significant increase in the infection rate over time, from 4.58% (2005) to 9.94% (2013). We analyzed the correlation (P < 0.01) between the occurrence of cysticercosis and the origin of the animals as well as between the viability of cysts and their location in the body. These results suggest that the occurrence of bovine cysticercosis in the mountainous region of Santa Catarina is high and at an alarming rate. Bovine cysticercosis can lead to an economic loss and can endanger public health. Therefore, government agencies need to plan and implement measures in order to control this disease.